Cervicovaginal Safety of the Formulated, Biguanide-Based Human Immunodeficiency Virus Type 1 (HIV-1) Inhibitor NB325 in a Murine Model. (24th October 2011) - Lozenski, Karissa; Kish-Catalone, Tina; Pirrone, Vanessa; Rando, Robert F.; Labib, Mohamed; Wigdahl, Brian; Krebs, Fred C.
Abstract : Vaginal microbicides that reduce or eliminate the risk of HIV-1 sexual transmission must do so safely without adversely affecting the integrity of the cervicovaginal epithelium. The present studies were performed to assess the safety of the biguanide-based antiviral compound NB325 in a formulation suitable for topical application. Experiments were performed using a mouse model of cervicovaginal microbicide application, which was previously shown to be predictive of topical agent toxicity revealed in microbicide clinical trials. Mice were exposed vaginally to unformulated NB325 or NB325 formulated in the hydroxyethyl cellulose "universal placebo." Following exposures to formulated 1% NB325 for 10 min to 24 h, the vaginal and cervical epithelia were generally intact, although some areas of minimal vaginal epithelial damage were noted. Although formulated NB325 appeared generally safe for application in these studies, the low but observable level of toxicity suggests the need for improvements in the compound and/or formulation.